Hexagon Theory dalam mendeteksi Fraudulent Financial Reporting Perusahaan BEI - Anna Falasifah; Kartika Hendra Titisari; Istiatin Istiatin (Penerbit Goodwood, 2025)
Purpose: This study aims to provide empirical evidence of the influence of the hexagon theory on financial reporting fraud in telecommunications companies on the IDX with an observation period of 2019-2023. Methodology/Approach: This study uses secondary data. The hexagon theory as an independent variable includes elements of stimulus, financial stability, external pressure, personal financial needs, opportunities, nature of industry, external auditor quality, capabilities, rationalization, ego and collusion. Financial reporting fraud is measured by the fraud score model. Results/Findings: Data analysis with multiple linear regression provides empirical evidence that financial stability, nature of industry, capabilities, and ego have an effect on financial reporting fraud. Conclusions: Not all elements of the Hexagon Theory are capable of detecting fraudulent financial reporting. Out of the six elements, only four can detect it: the pressure (stimulus) element from the FS proxy, the opportunity element from the NoI proxy, the rationalization element from the CIA proxy, and the ego element from the FNCP proxy. However, this does not apply to the other variables, which show no influence of the Hexagon Theory in detecting FFR. These variables include pressure (stimulus) from the FT, EP, and PFN proxies, opportunity from the IM and EAQ proxies, capability from the CID proxy, and collusion from the CWGP proxy. The independent variables in this study contribute 17.9% to FFR. Limitations: The study used purposive sampling with a sample size of 20 telecommunications companies listed on the IDX. This is a quantitative study with secondary data. Contribution: To reduce financial reporting fraud, management needs to pay attention to the stimulus factor from the Financial Stability (FS) proxy, opportunity from the Nature of Industry (NoI) proxy, rationalization from the Change in Auditor (CiA) proxy and ego from the frequent number of CEO's picture (FNCP) proxy.